2013
DOI: 10.3390/molecules19010067
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Ultrasound-Assisted Extraction of Phenolic Compounds from Polygonum cuspidatum

Abstract: Abstract:In this study the phenolic compounds piceid, resveratrol and emodin were extracted from P. cuspidatum roots using ultrasound-assisted extraction. Multiple response surface methodology was used to optimize the extraction conditions of these phenolic compounds. A three-factor and three-level Box-Behnken experimental design was employed to evaluate the effects of the operation parameters, including extraction temperature (30-70 °C), ethanol concentration (40%-80%), and ultrasonic power (90-150 W), on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 31 publications
1
33
1
Order By: Relevance
“…The results shown in the Fig. 4 are in accordance with those reported by [34] in the extraction of piceid, resveratrol and emodin in Polygonum cuspidatum with 50, 59, and 71% ethanol concentrations as extraction solvents. [28] also found that using 52% ethanol allowed the best extraction of phenolic peel compounds from Euryale ferox seeds.…”
Section: Effect Of Ethanol Concentrationsupporting
confidence: 90%
“…The results shown in the Fig. 4 are in accordance with those reported by [34] in the extraction of piceid, resveratrol and emodin in Polygonum cuspidatum with 50, 59, and 71% ethanol concentrations as extraction solvents. [28] also found that using 52% ethanol allowed the best extraction of phenolic peel compounds from Euryale ferox seeds.…”
Section: Effect Of Ethanol Concentrationsupporting
confidence: 90%
“…Piceid is the major derivative of resveratrol in many plants and is usually present in much higher amounts than resveratrol itself. The amount of piceid has been reported to be 3-7 times higher than that of resveratrol in grape berry skins, hop cones, grape juices, P. cuspidatum roots and cocoa-containing products [11][12][13]. It should be kept in mind that glycosylation of piceid to the resveratrol 3,5-β-D-diglucoside form increased the water solubility 1700-fold as compared to resveratrol [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different studies on the ultrasonic extraction of resveratrol indicate that the optimal extraction temperature is between 50 and 70°C. Hence, in this study the temperature was fixed at 60°C as recommended in the literature [3,14] The design of experiment (DOE) matrix was established with a Resolution (R) of V + (full factorial) and therefore the design did not suffer from confounding of the main effects and two-variable interaction effects and, furthermore, the two-variable interaction effects were not confounded with each other [15]. The total design matrix consisted of 8 (2 3 ) runs ( Fig.…”
Section: Full Factorial Design (Ffd) and Statistical Analysismentioning
confidence: 99%